This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ( x ) = x 5 and multiply the equation by ( x ) to get an exact equation, x 5 ( 2 y 2 + 4 x 2 ) dx x 4 y dy = 0 . Hence, F ( x, y ) = Z ( x 4 y ) dy = x 4 y 2 2 + h ( x ) F x = 4 x 5 y 2 2 + h ( x ) = x 5 M ( x, y ) = 2 x 5 y 2 + 4 x 3 h ( x ) = 4 x 3 h ( x ) = 2 x 2 99...
View
Full
Document
This note was uploaded on 03/29/2010 for the course MATH 54257 taught by Professor Hald,oh during the Spring '10 term at University of California, Berkeley.
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details